This action might not be possible to undo. Are you sure you want to continue?
27 Chapter 1
1.1.5 A sailboat sails for 1 hr at 4 km/hr (relative to the water) on a steady compass heading of 40◦ east of north. The saiboat is simultaneously carried along by a current. At the end of the hour the boat is 6.12 km from its starting point., The line from its starting point to its location lies 60◦ east of north. Find the x (easterly) and y (northerly) components of the water velocity. This is a straightforward relative velocity (vector addition) problem. Let vbl denote the velocity of the boat with respect to land, vbw the velocity of the boat with respect to the water and vwl the velocity of the water with respect to land. Then vbl = vbw + vwl where vbw = 4 km/hr @ 50◦ = (2.57ˆ + 3.06ˆ) km/hr x y ◦ vbl = 6.12 km/hr @ 30 = (5.3ˆ + 3.06ˆ) km/hr x y vwl = vbl − vbw = 2.73ˆ km/hr x 1.3.3 The vector r, starting at the origin, terminates at and speciﬁes the point in space (x, y, z). Find the surface swept out by the tip of r if (a) (r − a ) · a = 0 The vanishing of the dot product indicates that the vector r − a is perpendicular to the constant vector a. As a result, r − a must lie in a plane perpendicular to a. This means r itself must lie in a plane passing through the tip of a and perpendicular to a
r−a r a
(b) (r − a ) · r = 0 This time the vector r − a has to be perpendicular to the position vector r itself. It is perhaps harder to see what this is in three dimensions. However, for two dimensions, we ﬁnd
r−a a r
which gives a circle. In three dimensions, this is a sphere. Note that we can also complete the square to obtain (r − a ) · r = |r − 1 a |2 − | 1 a |2 2 2 Hence we end up with the equation for a circle of radius |a |/2 centered at the point a/2 |r − 1 a |2 = | 1 a |2 2 2 1.4.7 Prove that (A × B) · (A × B) = (AB)2 − (A · B )2 . This can be shown just by a straightforward computation. Since A × B = (Ay Bz − Az By )ˆ + (Az Bx − Ax Bz )ˆ + (Ax By − Ay Bx )ˆ x y z we ﬁnd |A × B |2 = (Ay Bz − Az By )2 + (Az Bx − Ax Bz )2 + (Ax By − Ay Bx )2
2 2 2 2 2 2 = A2 By + A2 Bz + A2 Bx + A2 Bz + A2 Bx + A2 By x x y y z z
− 2Ax Bx Ay By − 2Ax Bx Az Bz − 2Ay By Az Bz
2 2 2 = (A2 + A2 + A2 )(Bx + By + Bz ) − (Ax Bx + Ay By + Az Bz )2 x y z 2 2 2 where we had to add and subtract A2 Bx +A2 By +A2 Bz and do some factorization x y z to obtain the last line.
However, there is a more elegant approach to this problem. Recall that cross products are related to sin θ and dot products are related to cos θ. Then |A × B |2 = (AB sin θ)2 = (AB)2 (1 − cos2 θ) = (AB)2 − (AB cos θ)2 = (AB)2 − (A · B )2
1.5.5 The orbital angular momentum L of a particle is given by L = r × p = mr × v where p is the linear momentum. With linear and angular velocity related by v = ω × r, show that L = mr2 [ω − r(ˆ · ω )] ˆr Here, r is a unit vector in the r direction. ˆ Using L = mr × v and v = ω × r, we ﬁnd L = mr × (ω × r ) Because of the double cross product, this is the perfect opportunity to use the “BAC–CAB” rule: A × (B × C) = B(A · C) − C(A · B) L = m[ω(r · r ) − r(r · ω )] = m[ωr2 − r(r · ω )] Using r = r r, and factoring out r2 , we then obtain ˆ L = mr2 [ω − r(ˆ · ω )] ˆr (1)
1 1.5.6 The kinetic energy of a single particle is given by T = 2 mv 2 . For rotational motion 1 this becomes 2 m(ω × r )2 . Show that
T = 1 m[r2 ω 2 − (r · ω )2 ] 2 We can use the result of problem 1.4.7:
1 T = 2 m(ω × r )2 = 1 m[(ωr)2 − (ω · r )2 ] = 1 m[r2 ω 2 − (r · ω )2 ] 2 2
Note that we could have written this in terms of unit vectors
1 r T = 2 mr2 [ω 2 − (ˆ · ω)2 ]
Comparing this with (1) above, we ﬁnd that
1 T = 2L · ω
which is not a coincidence.
Chapter 3 3.2.4 (a) Complex numbers, a + ib, with a and b real, may be represented by (or are isomorphic with) 2 × 2 matrices: a + ib ↔ a −b b a
Show that this matrix representation is valid for (i) addition and (ii) multiplication. Let us start with addition. For complex numbers, we have (straightforwardly) (a + ib) + (c + id) = (a + c) + i(b + d) whereas, if we used matrices we would get a b −b a + c d −d c = (a + c) −(b + d) (b + d) (a + c)
which shows that the sum of matrices yields the proper representation of the complex number (a + c) + i(b + d). We now handle multiplication in the same manner. First, we have (a + ib)(c + id) = (ac − bd) + i(ad + bc) while matrix multiplication gives a b −b a c −d d c = (ac − bd) −(ad + bc) (ad + bc) (ac − bd)
which is again the correct result. (b) Find the matrix corresponding to (a + ib)−1 . We can ﬁnd the matrix in two ways. We ﬁrst do standard complex arithmetic (a + ib)−1 = a − ib 1 1 = = 2 (a − ib) a + ib (a + ib)(a − ib) a + b2
This corresponds to the 2 × 2 matrix (a + ib)−1 ↔ 1 + b2 a −b b a
Alternatively, we ﬁrst convert to a matrix representation, and then ﬁnd the inverse matrix −1 1 a −b a b (a + ib)−1 ↔ = 2 −b a a + b2 b a Either way, we obtain the same result. 3.2.19 An operator P commutes with Jx and Jy , the x and y components of an angular momentum operator. Show that P commutes with the third component of angular momentum; that is, [P , Jz ] = 0 We begin with the statement that P commutes with Jx and Jy . This may be expressed as [P , Jx ] = 0 and [P , Jy ] = 0 or equivalently as P Jx = Jx P and P Jy = Jy P . We also take the hint into account and note that Jx and Jy satisfy the commutation relation [Jx , Jy ] = iJz or equivalently Jz = −i[Jx , Jy ]. Substituting this in for Jz , we ﬁnd the double commutator [P , Jz ] = [P , −i[Jx , Jy ]] = −i[P , [Jx , Jy ]] Note that we are able to pull the −i factor out of the commutator. From here, we may expand all the commutators to ﬁnd [P , [Jx , Jy ]] = P Jx Jy − P Jy Jx − Jx Jy P + Jy Jx P = J x P Jy − J y P Jx − J x P Jy + J y P Jx =0 To get from the ﬁrst to the second line, we commuted P past either Jx or Jy as appropriate. Of course, a quicker way to do this problem is to use the Jacobi identity [A, [B, C]] = [B, [A, C]] − [C, [A, B]] to obtain [P , [Jx , Jy ]] = [Jx , [P , Jy ]] − [Jy , [P , Jx ]] The right hand side clearly vanishes, since P commutes with both Jx and Jy . 3.2.27 (a) The operator Tr replaces a matrix A by its trace; that is Tr (a) = trace(A) =
Show that Tr is a linear operator.
Recall that to show that Tr is linear we may prove that Tr (αA+βB) = α Tr (A)+ β Tr (B) where α and β are numbers. However, this is a simple property of arithmetic Tr (αA + βB) =
(αaii + βbii ) = α
aii + β
bii = α Tr (A) + β Tr (B)
(b) The operator det replaces a matrix A by its determinant; that is det(A) = determinant of A Show that det is not a linear operator. In this case all we need to do is to ﬁnd a single counterexample. For example, for an n × n matrix, the properties of the determinant yields det(αA) = αn det(A) This is not linear unless n = 1 (in which case A is really a single number and not a matrix). There are of course many other examples that one could come up with to show that det is not a linear operator.